ACQUIRED HAEMOPHILIA A - Koh, Ewe Jin; Tan, Jenq Tzong; Manan, Nur Nadia Amalina; Hor, Khai Yng; Teh, Zi Yu; Chin, Ming Lee (Journal of Ayub Medical College Abbottabad, 2023)
Acquired haemophilia A (AHA) is a rare disease believed to be caused by spontaneous inhibition of clotting Factor VIII by autoantibodies. This is in contrast to the more common congenital haemophilias which are largely due to an absolute deficiency in coagulation factors. It has a prevalence of approximately one per million per year. However, this figure may be underestimated because there are many undocumented cases due to a lack of recognition. Patients who develop this disease may present with catastrophic bleeding despite having no previous bleeding history. In this study, we report a case of acquired Haemophilia A presenting with spontaneous unprovoked bruising and discuss the approach to diagnosis and how to alert the clinician to suspect this potentially rare but devastating disease.